2009
DOI: 10.2174/1874913500902010011
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Language Contact and Vocabulary Knowledge on the Speaking Performance of Japanese Students of English

Abstract: This study examined the influence of language contact and vocabulary knowledge on the speaking performance of 73 Japanese students in English language schools in New Zealand. The participants completed a language contact profile questionnaire and a vocabulary test, and were administered a story retelling task (which constituted the measure of speaking performance). The results revealed that vocabulary knowledge correlated with fluency, accuracy, complexity, and global impression aspects of speaking performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The construct that she placed fifth “learns and uses English in context” also indicated the importance she gave to learning vocabulary in a meaningful context. According to the constructs she articulated, Teacher 2 also believed that students who “avoid using English unless it is really necessary” “experience problems in communication” due to their “limited vocabulary knowledge.” Oya, Manalo, and Greenwood (2009) revealed that vocabulary knowledge correlated with “fluency, accuracy, complexity, and global impression” aspects of speaking performance (p. 11). She believed that those who “do not like English .…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The construct that she placed fifth “learns and uses English in context” also indicated the importance she gave to learning vocabulary in a meaningful context. According to the constructs she articulated, Teacher 2 also believed that students who “avoid using English unless it is really necessary” “experience problems in communication” due to their “limited vocabulary knowledge.” Oya, Manalo, and Greenwood (2009) revealed that vocabulary knowledge correlated with “fluency, accuracy, complexity, and global impression” aspects of speaking performance (p. 11). She believed that those who “do not like English .…”
Section: Findings and Discussionmentioning
confidence: 99%
“…It can be explained that vocabulary knowledge (size, depth, antonym) has its own correlation with speaking proficiency (fluency, accuracy, etc.) Oya et al (2009), with research focusing on students' language contacts outside school (duration of stay, contact with friends, various places outside school) have correlation with speaking ability (fluency, accuracy, and complexity). As the participants are Japanese residing in an English-speaking country, this shows how much language contact outside of education institution has impact on speaking performance.…”
Section: Discussionmentioning
confidence: 99%
“…The word 'explain' means that it 'reveals' students' speaking proficiency based on their own vocabulary knowledge, size, depth and speed, which making a better view on relation between vocabulary and speaking. Oya et al, (2009), in their research found out that vocabulary knowledge correlated with fluency, accuracy, complexity, and global impression aspect of speaking performance. In addition, language contact outside of school was also has positive impact on speaking performance.…”
Section: Introductionmentioning
confidence: 95%
“…In general, research into the effect of vocabulary on speaking performance has not been conducted on a large scale [23]. Oya, Manalo and Greenwood [24] concluded that vocabulary was an influencing factor in students' ability to speak. Similarly to this, Koizumi and In'nami's [25] studies suggest that vocabulary knowledge is central to speaking proficiency.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%